2011
DOI: 10.1016/j.jviromet.2010.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of commercial systems for extraction of nucleic acids from DNA/RNA respiratory pathogens

Abstract: This study compared six automated nucleic acid extraction systems and one manual kit for their ability to recover nucleic acids from human nasal wash specimens spiked with five respiratory pathogens, representing Gram-positive bacteria (Streptococcus pyogenes), Gram-negative bacteria (Legionella pneumophila), DNA viruses (adenovirus), segmented RNA viruses (human influenza virus A), and non-segmented RNA viruses (respiratory syncytial virus). The robots and kit evaluated represent major commercially available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 17 publications
0
60
0
Order By: Relevance
“…Varma et al (2007) reported that extraction of large amounts of high-value, high molecular weight DNA can be limited by the presence of large amounts of phenolic compounds, DNases, and organelle DNA. Some DNA extraction methods have numerous potential limitiations, including risks of cross-contaminations because of the large number of steps involved, lower molecular mass of extracted DNA because of degradation, and samples that are unsuitable for high-throughput applications because of the longer extraction time required (Tan and Yiap, 2009;Turci et al, 2011;Yang et al, 2011). In this study, 2 modified methods (cited here as Methods I and II) were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Varma et al (2007) reported that extraction of large amounts of high-value, high molecular weight DNA can be limited by the presence of large amounts of phenolic compounds, DNases, and organelle DNA. Some DNA extraction methods have numerous potential limitiations, including risks of cross-contaminations because of the large number of steps involved, lower molecular mass of extracted DNA because of degradation, and samples that are unsuitable for high-throughput applications because of the longer extraction time required (Tan and Yiap, 2009;Turci et al, 2011;Yang et al, 2011). In this study, 2 modified methods (cited here as Methods I and II) were compared.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of both RNA extraction and subsequent amplification can contribute to differences with regard to LOD. Use of different specimen types and RNA extraction protocols significantly influences the performance of the diagnostic procedures (35). In addition, molecular diagnostics of RNA viruses depends on reverse transcription (RT)-conventional PCR or RT-qPCR, a two-step process highly influenced by the choice of reagents (36).…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…A screening test that could detect women carrying GBS during labor could eliminate the need for prenatal screening at 35-37 weeks and reduce the risk of antibiotic prophylaxis for noncolonized women (3,6 ). The screening test must include a sample preparation method that ensures high recovery of nucleic acids and sufficient purity of clinical samples to control inhibitors (7,8 ). Comparative performance studies of automated extraction platforms have demonstrated the direct correlation between the performance of the extraction system and the imprecision of a molecular assay (7)(8)(9).…”
Section: © 2014 American Association For Clinical Chemistrymentioning
confidence: 99%